Modal sosial dalam peningkatan kesejahteraan nelayan (Studi kasus kelompok nelayan Sikuyuh di Kelurahan Lapulu Kecamatan Abeli Kota Kendari) - Amir, Fitriah; Haeruddin (Universitas Halu Oleo, 2024)
The purpose of this research is to discover how social capital is organised within a fishing community and analyse how social capital affects the well-being of fishermen in the Sikuyuh fishing community. The research variables include fishermen's household welfare, norms, networks, and trust levels. The influence of several components of social capital was analyzed using multiple regression techniques. Data were collected through interviews, questionnaire, observations, and documentation, while the research sample used census method. Variables were measured using a Likert scale and score-based assessments for each indicator. The study results reveal that the presence of social capital in the Sikuyuh fishing group encompasses norms that are implemented and upheld in the community. Social interactions within the group provide benefits to fishermen, such as collaboration in mutual aid activities, sharing information, and offering mutual support to sustain their livelihoods. High levels of trust among fishermen foster strong relationships and help prevent potential conflicts within the Sikuyuh fishing group. The multiple regression analysis produced the equation: Y = 1.247 + 0.126X₁ + 0.589X₂ + 0.329X₃. This equation shows that fishermen's household welfare (Y) is influenced by three variables: norms (X₁), networks (X₂), and trust (X₃). It reveals that the analyzed components of social capital significantly impact the welfare of fishermen's households. This finding emphasizes that the higher the social capital possessed by members of the Sikuyuh fishing group, the greater its positive impact on their household welfare.